Uji Potensi Bakteri Selulotik dari Lahan Pertanian yang Tercemar Pestisida - Setia Budi, Putu; Wayan Gunam, Ida Bagus; Dewi Anggreni, Anak Agung Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 1 (2016): Maret)
The aim of this study was to  isolate bacteria that could potentially degrade the cellulose from of agricultural land in the village  Candikuning Bedugul and to determine the ability of isolates in degrade cellulose.These  bacteria are capable of utilizing cellulose as carbon source 11 only isolates that produce a clear zone with diameters above 12.07 mm up to 45.59 mm on Gram ’sIodine test.  Eleven isolates bacteria cellulolytic pure who afford occurrence bacterial growth on media selective and isolates produce clear zone that most highest is CK 18. Keywords: cellulose degrading bacteria, isolation, Gram's Iodine test.
Keywords: 85,